Nitrogen diffusion in the Nb-2.0wt%Ti measured by mechanical spectroscopy - Grandini, Carlos Roberto [UNESP]; da Silva, Luciano Monteiro [UNESP]; de Almeida, Luciano Henrique [UNESP]; Florencio, Odila; Zschommler Sandim, Hugo Ricardo (Trans Tech Publications Ltd, 2008)
Metals that present bcc crystalline structure, when receiving addition of interstitial atoms as oxygen, nitrogen, hydrogen and carbon, undergo significant changes in their physical properties, being able to dissolve great amounts of those interstitial elements, thus forming solid solutions. Niobium and most of its alloys possess bcc crystalline structure and, as Brazil is the largest world exporter of this metal, it is fundamental to understand the interaction mechanisms between interstitial elements and niobium or its alloys. In this paper, mechanical spectroscopy (internal friction) measurements were performed in Nb-2.0wt%Ti alloys containing nitrogen in solid solution. The experimental results presented complex internal friction spectra and with the addition of substitutional solute, it was observed interactions between the two types of solutes (substitutional and interstitial), considering that the random distribution of the interstitial atoms was affected by the presence of substitutional atoms. Interstitial diffusion coefficients, pre-exponential factors and activation energies were calculated for nitrogen in the Nb-2.0wt%Ti alloys.
Keywords: diffusion; Nb-Ti alloys; nitrogen